The Symbolism of Prestige: An Archaeological Example from the Royal Cemetery of Ur - Pollock, Susan Marsha (1983)
Ph.D. Dissertation; Chairman: Henry T.Wright. Order No. DA8324264; cf. DissAbstr 44,6 (1983) 1847-A.